The influence of snowball throwing learning method on students’ self-efficacy - Suci Dahlya Narpila; Izwita Dewi; Faiz Ahyaningsih (AXIOM : Jurnal Pendidikan dan Matematika, 2026)
This study was motivated by the finding that students’ self-efficacy at MTsS Hifzhil Qur’an was relatively low. Further investigation revealed that this issue was associated with the teaching methods employed by the teachers. Therefore, implementing innovative instructional strategies is necessary to enhance students’ self-efficacy. Among various instructional approaches, the Snowball Throwing method is considered a promising strategy for addressing this issue. Accordingly, this study aimed to examine whether the Snowball Throwing method has a significant effect on students’ self-efficacy. This study employed an experimental design involving 60 seventh-grade students, comprising one experimental class and one control class. The research instrument was a student self-efficacy questionnaire developed based on established self-efficacy indicators. The collected data were analyzed using an independent-samples t-test, which yielded a p-value of 0.005. Since this value was lower than the significance level of 0.05, the findings indicate that the Snowball Throwing method had a significant positive effect on students’ self-efficacy. Therefore, this method may be considered an effective instructional approach for improving students’ self-efficacy.